N-glycans in lung tissue specimens: a prospective target for enhanced cancer diagnosis and prognosis - Erika Lattova; Jana Skrickova; Jitka Hausnerova; Karolina Krystofova; Zbynek Zdrahal; Leos Kren; Mikulas Popovic (Journal of Translational Medicine)
Abstract Background It is well established that the cancerous transformation of cells is accompanied by profound alterations in glycosylation. In this study, we demonstrate the diagnostic potential of N-glycan profiling in tissue specimens from patients, primarily representing the two major types of lung cancer: non-small cell and small cell lung cancer. Methods Lung tissues and biopsies obtained from surgery and bronchoscopy underwent sample processing and enzymatic digestion. After labeling, glycans were analyzed employing matrix-assisted laser desorption/ionization mass spectrometry. Statistical analysis was conducted using methods following principles of compositional data analysis. Results Comparison of glycan profiles demonstrated an increase in paucimannose and high mannose glycans in most tumor specimens, including those with inflammation and histological negative for malignancy. Cancerous tissues exhibited more profound changes in glycosylation. Despite the high heterogeneity in profiles, two main groups of not detected glycans in peritumoral tissues, considered as controls, were observed to correlate with cancer progression in patients. One with complex polylactosamine multifucosylated glycans frequently harboring terminal N-acetyl-glucosamine residues. These glycans were present in most tumors, with their numbers and intensities increasing as cancer progressed. In contrast, the second group exhibited polylactosamine glycans sporadically. Instead, the biopsies of several patients with rapid progression displayed a significant presence in a set of tri- and tetra-antennary core fucosylated glycans having mostly unoccupied N-acetyl-glucosamine residues unless carrying additional fucose unit(s). Conclusions The results imply distinct glycosylation patterns even in patients with the same histological type of lung cancer, supporting trends toward personalized diagnosis and more tailored therapies. Currently, tissue biopsies remain the gold standard for diagnosing premalignant and malignant lesions in the lung. Expanded knowledge on glycosylation in these lesions could contribute to improved diagnostic accuracy and better monitoring of malignant disease progression in clinical practice. Graphical abstract